2014
DOI: 10.1111/maec.12116
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, distribution and habitat preference of Hippocampus guttulatus and Hippocampus hippocampus in a semi‐enclosed central Mediterranean marine area

Abstract: Population abundance, distribution and habitat preference of the Mediterranean sympatric seahorses Hippocampus guttulatus and Hippocampus hippocampus were investigated in a semi‐enclosed sea system (Apulian coast, Ionian Sea). A total of 242 individuals of seahorses were sighted in the 11 transects surveyed in summer 2011. Hippocampus guttulatus (n = 225) were 14 times more abundant than H. hippocampus (17). The mean abundance of H. guttulatus for all the pooled sites was 0.018 m−2 (SE ± 0.003) ranging from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
65
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 24 publications
10
65
2
1
Order By: Relevance
“…Other researchers (Foster and Vincent 2004, Curtis and Vincent 2005, 2006, Vincent et al 2011 reported that H. guttulatus inhabited seagrass-or algal beds. The presently reported study is also in partial disagreement with the recent work of Gristina et al (2014), who also studied the Mar Piccolo of Taranto. The above-mentioned authors described H. guttulatus with no habitat preference between algal beds and hard substrates.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Other researchers (Foster and Vincent 2004, Curtis and Vincent 2005, 2006, Vincent et al 2011 reported that H. guttulatus inhabited seagrass-or algal beds. The presently reported study is also in partial disagreement with the recent work of Gristina et al (2014), who also studied the Mar Piccolo of Taranto. The above-mentioned authors described H. guttulatus with no habitat preference between algal beds and hard substrates.…”
Section: Discussioncontrasting
confidence: 56%
“…(Results of another study on this population were only recently published by Gristina et al 2014). We would like to emphasize the importance of this lagoon as an important naturalistic area and a refuge for this vulnerable species.…”
mentioning
confidence: 99%
“…Las aguas eutrofizadas han favorecido también la presencia de caballitos de mar en el mar Piccolo di Taranto, en Italia, debido al incremento de las poblaciones de crustáceos, presas potenciales de estos peces, según sugieren Gristina et al (2015). Rosa et al (2007) encontraron que la disponibilidad de hábitats parece influir en la abundancia y distribución espacial de la especie H. reidi, sugerida por el uso de briozoos y macroalgas abundantes en las estaciones de la costa sur de Brasil, mientras que las raíces de mangle lo fueron en las estaciones de la costa norte.…”
Section: Discussionunclassified
“…Where algae are absent, large numbers of sabellids, mollusks and ceriantharia have colonized the soft bottom (Gristina et al, 2013). The macrozoobenthic community is unique and characterized by very rich assemblages of filter feeders (mainly consisting of sponges, hydrozoans, polychaetes, bryozoans, mollusks, crinoids and tuinicates) that colonize all types of hard substrates forming pluristratified assemblages (Gristina et al, 2013).…”
Section: Seafloor Integrity Of Thementioning
confidence: 99%
“…Others have focused on the accumulation of dangerous compounds in the Mar Piccolo Basin waters and sediments (Buccolieri et al, 2006;Calace et al, 2005;Cardellicchio et al, 2007;Petronio et al, 2012). Nevertheless, the area hosts several species protected by the Barcelona convention (Cardone, Corriero, & Gaino, 2010;Cerruti, 1938;Gristina et al, 2013;Parenzan, 1969;Matarrese et al, 2004) and received several conservation designations: Site of Community Importance (SCI; IT9130004 -EU Habitats Directive 92/43/CEE) and a Regional Reserve ('Palude La Vela' EUAP1189) along the eastern coast (Figure 1).…”
Section: Seafloor Integrity Of Thementioning
confidence: 99%